2023
DOI: 10.1001/jamapsychiatry.2022.3860
|View full text |Cite
|
Sign up to set email alerts
|

Association of Treatment-Resistant Depression With Patient Outcomes and Health Care Resource Utilization in a Population-Wide Study

Abstract: ImportanceThe totality of the societal and individual impact of treatment-resistant depression (TRD) is unknown, as is the potential to prognosticate TRD. The generalizability of many observational studies on TRD is limited.ObjectiveTo estimate the burden of TRD in a large population-wide cohort in an area with universal health care by including data from both health care types (psychiatric and nonpsychiatric) and, further, to develop a prognostic model for clinical use.Design, Setting, and ParticipantsThis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…47 Although PD is among the most common comorbid psychiatric conditions in TRD, none of these studies reported on participants with both TRD and PD. [48][49][50] Our study supports previous studies showing that a pharmacotherapy including quetiapine can improve subjective sleep in TRD independently of the presence of PD or not. However, we found a greater improvement of sleep quality in TRD/PD+ compared with TRD/PD− treated with a pharmacotherapy, which included quetiapine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…47 Although PD is among the most common comorbid psychiatric conditions in TRD, none of these studies reported on participants with both TRD and PD. [48][49][50] Our study supports previous studies showing that a pharmacotherapy including quetiapine can improve subjective sleep in TRD independently of the presence of PD or not. However, we found a greater improvement of sleep quality in TRD/PD+ compared with TRD/PD− treated with a pharmacotherapy, which included quetiapine.…”
Section: Discussionsupporting
confidence: 90%
“…In a 20-week open trial with quetiapine (315 ± 109 mg, flexible dose), 14 patients with TRD showed a decrease of more than 4 points on the TSS at their first time of measurement (eg, after only 2 weeks of treatment) 47 . Although PD is among the most common comorbid psychiatric conditions in TRD, none of these studies reported on participants with both TRD and PD 48–50 . Our study supports previous studies showing that a pharmacotherapy including quetiapine can improve subjective sleep in TRD independently of the presence of PD or not.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, results of a recent analysis in the WHO World Mental Health Surveys underscores that persistence with next-step treat ments is uncommon in persons with MDD 82 . Also, in those who do switch to nextstep treat ments, a considerable treatment delay (i.e., 6-9 months) elapses before switching occurs 82,83 .…”
Section: Definitions Of Treatment-resistant Depressionmentioning
confidence: 99%
“…The exclusion criteria mainly included the following: (1) subjects who had a suicide attempt within the last year, a currently significant risk of suicide, or a score ⩾3 points on Item 3 (suicide assessment) of the HAMD-17; (2) subjects with a current psychiatric diagnosis other than depression; (3) subjects with unstable cardiovascular, hepatic, renal, blood, endocrine, or other medical diseases; (4) subjects with any neurological disease (such as Parkinson's disease, cerebrovascular accident and epilepsy) or cerebral injury (traumatic or diseaserelated injury); (5) subjects with clinically significant abnormal laboratory values; (6) subjects who used at least two different antidepressants with the recommended dose and an adequate duration of treatment (maximum dosage for at least 4 weeks journals.sagepub.com/home/tpp TherapeuTic advances in psychopharmacology according to the label) and still had no response; (7) subjects who had received regular antidepressant treatment in the 2 weeks prior to screening; (8) subjects who received electroconvulsive therapy (ECT), transcranial magnetic stimulation, or other physical therapy within 3 months; (9) subjects who had a history of substance abuse (including alcohol, drug or other psychoactive substance abuse) within 1 year before screening; and (10) women who were pregnant, breastfeeding, or serum human chorionic gonadotropin (HCG) (+) on screening or were planning to become pregnant. A more detailed list of the inclusion/ exclusion criteria can be found at http://clinicaltrials.gov (NCT03183505).…”
Section: Patient Selectionmentioning
confidence: 99%
“…However, despite the availability of antidepressants in multiple classes, almost one-third of MDD patients do not respond to conventional antidepressant medications. 4,5 Thus, there is an urgent need to develop novel treatments for MDD.…”
Section: Introductionmentioning
confidence: 99%